2022
DOI: 10.22270/ajdhs.v2i1.10
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review on Nutraceuticals and its Application

Abstract: Because of their putative safety, nutraceuticals have sparked tremendous interest. Nutraceuticals are nutritional supplements that are used to improve health, postpone aging, prevent disease and support the healthy functioning of the human body. Nutraceuticals are currently gaining popularity due to their nutritional and medicinal properties. They are classified as dietary supplements or herbal bioactive substances based on their source. Herbal nutraceuticals aid in the maintenance of health and the promotion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Research studies and findings which proposed a possible connection between premenstrual syndrome, prolactin levels, prostaglandins and γ-linolenic acid, an essential fatty acid precursor of prostaglandin E1, originate from the early 1980s 72, 73 , including first clinical studies showing success in the treatment with Oenothera oil, for premenstrual syndrome 74 and mastalgia 75 . Data showed that women with premenstrual syndrome have the inability to convert linoleic acid to γlinolenic acid due to a decreased activity of the delta-6 desaturase enzyme 76,82 , in addition to hormonal disbalance 71 . Cerin et al 71 investigated hormonal status (progesterone, estradiol, prolactin, cortisol, aldosterone) and cholesterol, triglyceride, lipoprotein, magnesium and calcium levels, and glucose tolerance in the follicular and luteal phases of the menstrual cycle in women diagnosed with premenstrual syndrome vs. symptom-free controls.…”
Section: Evening Primrose (Oenothera Biennis L)mentioning
confidence: 99%
“…Research studies and findings which proposed a possible connection between premenstrual syndrome, prolactin levels, prostaglandins and γ-linolenic acid, an essential fatty acid precursor of prostaglandin E1, originate from the early 1980s 72, 73 , including first clinical studies showing success in the treatment with Oenothera oil, for premenstrual syndrome 74 and mastalgia 75 . Data showed that women with premenstrual syndrome have the inability to convert linoleic acid to γlinolenic acid due to a decreased activity of the delta-6 desaturase enzyme 76,82 , in addition to hormonal disbalance 71 . Cerin et al 71 investigated hormonal status (progesterone, estradiol, prolactin, cortisol, aldosterone) and cholesterol, triglyceride, lipoprotein, magnesium and calcium levels, and glucose tolerance in the follicular and luteal phases of the menstrual cycle in women diagnosed with premenstrual syndrome vs. symptom-free controls.…”
Section: Evening Primrose (Oenothera Biennis L)mentioning
confidence: 99%
“…But these biomarkers have not proven adequate for cancer screening. Therefore, several researchers have resorted to the study of extract patterns of abnormally expressed proteins, peptide fragments, glycans and autoantibodies from serum, urine, ascites or tissue samples from cancer patients [16][17][18][19] . With the development of proteomics technology, protein biomarkers for many cancers have been discovered.…”
Section: Nanotechnology Used In Cancer Biomarker Screeningmentioning
confidence: 99%
“…ese naturally occurring bioactive or chemical compounds function not only as nutritional supplements but also showcase properties that promote health, cure diseases, or possess preventive capabilities [6,7]. Constituted of essential components such as lipids, vitamins, carbohydrates, proteins, and minerals, nutraceuticals have demonstrated potential e cacy in treating a range of diseases including cardiovascular diseases, diabetes, atherosclerosis, cancer, and problems associated neurological conditions [8][9][10]. e inclination towards nutraceuticals can be attributed to several factors [11][12][13][14][15]:…”
mentioning
confidence: 99%